2014
DOI: 10.1002/anie.201308002
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of a Diphosphagermylene through pπ–pπ Interactions with a Trigonal‐Planar Phosphorus Center

Abstract: N-Heterocyclic carbenes and their heavier homologues are, in part, stabilized by delocalization of the N lone pairs into the vacant p-orbital at carbon (or a heavier Group 14 element center). These interactions are usually absent in the corresponding P-substituted species, owing to the large barrier to planarization of phosphorus. However, judicious selection of the substituents at phosphorus has enabled the synthesis of a diphosphagermylene, [(Dipp)2P]2 Ge, in which one of the P centers is planar (Dipp=2,6-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 50 publications
3
46
0
Order By: Relevance
“…reported monomeric [{2,6‐(2,4,6‐Me 3 C 6 H 2 ) 2 C 6 H 3 }(Ph)P] 2 Sn in 2007 and recently Izod and co‐workers reported crystallographically characterized stannylenes and germylenes ([Trip 2 P] 2 Sn and [Dipp 2 P] 2 E with E=Sn, Ge; Dipp=2,6‐ i Pr 2 C 6 H 3 ) demonstrating unique bonding features involving Sn–P and Ge–P π‐interaction . Very recently a cyclic alkyl(amino) carbene (cAAC) anchored silylene with two phosphinidenes was reported by Roesky, however, its reactivity has not been explored yet . As an alternative to mesomeric stabilization, which is common for aminotetrylenes, phosphanyltetrylenes are prone to formation of mutual donor–acceptor complexes with increased coordination sphere .…”
Section: Methodssupporting
confidence: 55%
“…reported monomeric [{2,6‐(2,4,6‐Me 3 C 6 H 2 ) 2 C 6 H 3 }(Ph)P] 2 Sn in 2007 and recently Izod and co‐workers reported crystallographically characterized stannylenes and germylenes ([Trip 2 P] 2 Sn and [Dipp 2 P] 2 E with E=Sn, Ge; Dipp=2,6‐ i Pr 2 C 6 H 3 ) demonstrating unique bonding features involving Sn–P and Ge–P π‐interaction . Very recently a cyclic alkyl(amino) carbene (cAAC) anchored silylene with two phosphinidenes was reported by Roesky, however, its reactivity has not been explored yet . As an alternative to mesomeric stabilization, which is common for aminotetrylenes, phosphanyltetrylenes are prone to formation of mutual donor–acceptor complexes with increased coordination sphere .…”
Section: Methodssupporting
confidence: 55%
“…In contrast to the X‐ray crystal structure of 3 e , the DFT‐optimized geometry of cation 3 a shows a significantly elongated Ge−P1 bond (2.342 Å) and a strongly pyramidalized geometry around the P1 atom (Σ°P1=337°), which is consistent with only a weak or no Ge−P‐π‐interaction . In fact, the calculated Ge−P1 bond length is similar to those observed for the push–spectator‐type diphosphinogermylene [(Dipp 2 P) 2 Ge:] (Ge−P: 2.234 and 2.382 Å) .…”
Section: Figurementioning
confidence: 99%
“…We calculated the singlet–triplet energy gaps Δ E S–T of the germylene compounds 5 – 7 (Table ) and found that 6 would be relatively less stable compared to the other studied Ge II systems. Divalent systems frequently dimerize under normal experimental conditions . In the dimerization mechanism, each of the filled σ orbitals of singlet germylene system interacts with the empty p orbital and forms a Ge=Ge double bond.…”
Section: Resultsmentioning
confidence: 99%
“…Divalent systems frequently dimerize under normale xperimental conditions. [21][22][23]64] In the dimerization mechanism, each of the filled s orbitals of singlet germylene system interacts with the empty po rbital and forms aG e =Ge double bond.S uch dimer formation are possible when the sum of the DE S-T valueso ft wo interacting germylenes is smaller than the corresponding Ge=Ge double-bond energy. [23b] We have examined the possibility for the formation of double bondedd imer compound for 5 and 7.I nt he case of compound 5,t he calculated double bond energy is relatively smaller (À39.5 kcal mol À1 )t han the sum of the DE S-T value (60.6 kcal mol À1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation